Wavelet Transform Based Methods for Fault Detection and Diagnosis of HVDC Transmission Systems - (:unkn) unknown (My University, 2019)
ABSTRACT WAVELET TRANSFORM BASED METHODS FOR FAULT DETECTION AND DIAGNOSIS OF HVDC TRANSMISSION SYSTEMS by Zhonxguan Li The University of Wisconsin-Milwaukee, 2019 Under the Supervision of Professor Lingfeng Wang High-voltage direct current (HVDC) is a key enabler in power system. HVDC offers a most efficient means of transmitting large amount of power. Applications of HVDC can improve the operation security, reliability performance and economy of power systems. Due to factors inside and outside the HVDC system, the system will experience various faults, which have infected HVDC system. VSC-HVDC is a HVDC transmission based on IGBT and PWM. VSC-HVDC direct current transmission has broad application prospects in new energy grid-connected and grid-connected transformation. In this research, aiming at the fault diagnosis of VSC-HVDC, the fault diagnosis and fault detection are studied. In this research, a VSC-HVDC was simulated in MATLAB Simulink, and an adjusted VSC-HVDC model was built. The models were applied to simulate the basic operation of VSC-HVDC and main faults on AC and DC side in the VSC-HVDC system. Take line current on AC or DC side as input data, the result data after wavelet processing was applied in HVDC faults diagnosis. To verify the function of fault detection, DC faults at different locations were set in the adjusted model. Wavelet entropy was applied in fault diagnosis and detection to gather accurate results. According to the simulation results, wavelet transform exhibits a good performance in HVDC fault diagnosis and detection.
Keywords: Faults detection; Faults diagnosis; HVDC; wavelet transform